Penerapan Model UTAUT 2 Untuk Menganalisis Penerimaan Dan Penggunaan Aplikasi E-Wallet Di Kabupaten Kuningan - Syamfithriani, Tri Septiar; Trisudarmo, Ragel; Mirantika, Nita (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2024)
The rapid advancement of technology has significantly impacted various aspects of life, including payments and financial transactions using e-wallet applications. Kuningan Regency possesses a considerable economic potential and numerous opportunities to enhance the business and technology sectors through the use of e-wallet applications. In adopting e-wallet application technology, understanding the factors influencing its acceptance and usage is crucial. One model employed for comprehending these factors is the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2), which focuses on seven key elements influencing the acceptance and use of technology: performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit. This research aims to identify the factors influencing the acceptance and use of e-wallet applications using the UTAUT 2 model, with the addition of the security factor in e-wallet applications. The study involves a quantitative method with 397 respondents, and data analysis using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach with the assistance of SmartPLS version 3.0. The results indicate that performance expectancy, facilitating conditions, hedonic motivation, and habit play crucial roles in shaping the intention to use e-wallet applications in Kuningan Regency. These factors are able to explain 68.5% of the research model, the remaining 31.5% is explained by other variables. Understanding these factors allows for efforts to enhance the acceptance and use of e-wallet applications in Kuningan Regency, so that it can help improve the economy.